Effective inactivation of a wide range of viruses by pasteurization. Issue 1 (16th November 2017) - Gröner, Albrecht; Broumis, Connie; Fang, Randel; Nowak, Thomas; Popp, Birgit; Schäfer, Wolfram; Roth, Nathan J.
Abstract : BACKGROUND: Careful selection and testing of plasma reduces the risk of blood‐borne viruses in the starting material for plasma‐derived products. Furthermore, effective measures such as pasteurization at 60°C for 10 hours have been implemented in the manufacturing process of therapeutic plasma proteins such as human albumin, coagulation factors, immunoglobulins, and enzyme inhibitors to inactivate blood‐borne viruses of concern. A comprehensive compilation of the virus reduction capacity of pasteurization is presented including the effect of stabilizers used to protect the therapeutic protein from modifications during heat treatment. STUDY DESIGN AND METHODS: The virus inactivation kinetics of pasteurization for a broad range of viruses were evaluated in the relevant intermediates from more than 15 different plasma manufacturing processes. Studies were carried out under the routine manufacturing target variables, such as temperature and product‐specific stabilizer composition. Additional studies were also performed under robustness conditions, that is, outside production specifications. RESULTS: The data demonstrate that pasteurization inactivates a wide range of enveloped and nonenveloped viruses of diverse physicochemical characteristics. After a maximum of 6 hours' incubation, no residual infectivity could be detected for the majority of enveloped viruses. Effective inactivation of a range of nonenveloped viruses, with the exception of nonhuman parvoviruses, was documented. CONCLUSION: Pasteurization is a very robust and reliable virus inactivation method with a broad effectiveness against known blood‐borne pathogens and emerging or potentially emerging viruses. Pasteurization has proven itself to be a highly effective step, in combination with other complementary safety measures, toward assuring the virus safety of final product.